THE CONCEPT OF ‘ALA BỤ ALA’: A SIGNAL FOR IGBO EXTINCTION - CYPRIAN CHIDOZIE EZE; MABEL NKECHINYERE EZE (International Studies Journal)
Igbo people has been known as the ethnic group that is most travelled. They do not only travel but also prosper in foreign lands, build houses, feel at home and relax in another man’s land. Some marry from other ethnic groups, bear children and imbibe the culture of other people they meet in the host community. Some do not care to reach their native land or build any house in their state or village in spite of the prosperity they have gotten. This behaviour has been popularly tagged as Alabụala meaning, land is land. Many have written on the Igbo language endangerment especially since the prediction of the United Nations Educational, Scientific and Cultural Organization(UNESCO) that Igbo language may be heading to extinction in fifty years if nothing is done by the speakers. None has emphasized the Igbo belief in travelling live and not just travelling but relaxing in foreign land and neglecting of their heritage community. This attitude has been described as Alabụala meaning land is land. The aim of this paper is to expose the danger of this type of attitude demonstrated by some Igbo indigenes to the continuity of Igbo language and culture. It also suggests ways to prevent the extinction of the language and culture. In doing this, the researchers made use of participatory observation in data collection. Participatory in that, he lives in Diaspora. Some Igbo youths were also interviewed to investigate their familiarity with their heritage land and their ability to speak Igbo language.